EFFECT OF LEARNING MODEL LEARNING CYCLE BASED CONCEPT MAP OF RESULTS OF STUDENT LEARNING IN THE MATTER OF DYNAMIC ELECTRICAL - Karya Sinulingga (Jurnal Pendidikan Fisika, 2013)
The objective of this research to: 1) Determine the influence of the learning model Learning Cycle based Concept Mapping on learning outcomes of students in the subject matter in class X Dynamic Electricity second semester SMA Swasta Parulian 1 Medan TP 2011/2012. 2) Determine the influence of conventional learning model on learning outcomes of students in the subject matter Dynamic Electricity in class X SMA Swasta Parulian 1 Medan TP 2011/2012. 3) Knowing how student activity during the learning process by using a model-based Learning Cycle Concept Map. The research was quasi-experimental with the entire population of students of class X SMA Swasta Parulian 1 Medan consisting of 4 classes. Samples were taken 2 classes are determined by random cluster sampling technique, the Class X-2 by using a model-based Learning Cycle Concept Map and the class X-1 using conventional learning models. The results showed the average value of the experimental class pretest was 40.14 and 40.28 in the control class. After treatment in each class earned an average post-test score in the experimental class was 75.43 while the control class is 64.42. On the hypothesis testing results obtained t > ttable ie 4.54 > 1.66 at significance level α = 0.05 and df = 68. This means that Ha received or no influence Learning Cycle Model-Based Concept Map on learning outcomes of students in the subject matter Dynamic Electricity in class X SMA Swasta Parulian 1 Medan second semester TP 2011/2012.